2021
DOI: 10.1186/s12879-021-06005-x
|View full text |Cite
|
Sign up to set email alerts
|

Chorea as the presenting feature of acute rheumatic fever in childhood; case reports from a low-prevalence European setting

Abstract: Background Despite a notable decrease in acute rheumatic fever (ARF) incidence in the past few decades, there are still cases in our setting. Sydenham chorea (SC) may be the initial manifestation for this condition in childhood in a significant proportion of children. We report two cases of choreoathetosis in children as the first manifestation of ARF. Case presentation A previously healthy 8-year-old boy presented with right hemichorea with a pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 11 publications
0
31
0
1
Order By: Relevance
“…Sydenham’s disease is the most common cause of acquired chorea in children, and often presents asymmetrically or unilaterally [ 8 71 ]. Although there are few cases currently seen in resource-rich countries, it remains quite prevalent in many resource-limited countries [ 71 ]. Although known for its asymmetry, in one follow-up study of 65 children, 78% were reported as generalized versus 22% hemichorea.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sydenham’s disease is the most common cause of acquired chorea in children, and often presents asymmetrically or unilaterally [ 8 71 ]. Although there are few cases currently seen in resource-rich countries, it remains quite prevalent in many resource-limited countries [ 71 ]. Although known for its asymmetry, in one follow-up study of 65 children, 78% were reported as generalized versus 22% hemichorea.…”
Section: Resultsmentioning
confidence: 99%
“…The etiology of Sydenham’s disease is proposed to be an autoimmune response generated by antibodies to streptococcus A, often in the setting of rheumatic fever. Onset of symptoms is generally 1–8 months after the acute infection, although cases are reported of abnormal movements as the presenting symptom [ 71 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…We identified 1479 patients with IPD (median [IQR] age at onset, 10 [8-13] years in 1354 patients; 985 of 1426 [69.1%] female and 441 of 1426 [30.9%] male) were identified from 307 articles…”
Section: Resultsmentioning
confidence: 99%
“…Sydenham chorea represents the most common cause of acquired chorea in childhood [1]. It is one of the major criteria for the diagnosis of acute rheumatic fever [2]. In Sydenham chorea there is both neurological abnormalities and psychiatric disorder.…”
Section: Introductionmentioning
confidence: 99%
“…The neurological abnormalities comprise of involuntary choreatic movements, incoordination of voluntary movement, muscular weakness and hypotonia [3]. Psychiatric disorders include emotional lability, hyperactivity, distractibility, obsessions and compulsions [2,3]. Choreatic movements are involuntary, irregular, purposeless, non-rhythmic, abrupt, rapid and unsustained.…”
Section: Introductionmentioning
confidence: 99%